(untitled) (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2024)
The term uterine smooth muscle tumor of uncertain malignant potential (STUMP) refers to a group of uterine smooth muscle tumors (SMT) that cannot be unequivocally diagnosed as benign or malignant. The diagnosis, surgical management and follow-up of this pathology remain controversial, especially in women of childbearing age with a desire for fertility, due to the non aggressive behavior and the prolonged survival rate compared to leiomyosarcomas. However, recidivism is estimated between 8.7% and 11%. We reported the case of two patients treated by surgical intervention